2019
DOI: 10.3389/fcell.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

Similarities Between Embryo Development and Cancer Process Suggest New Strategies for Research and Therapy of Tumors: A New Point of View

Abstract: Here, I propose that cancer stem cells (CSCs) would be equivalent to para-embryonic stem cells (p-ESCs), derived from adult cells de-re-programmed to a ground state. p-ESCs would differ from ESCs by the absence of genomic homeostasis. A p-ESC would constitute the cancer cell of origin (i-CSC or CSC0), capable of generating an initial tumor, corresponding to a pre-implantation blastocyst. In a niche with proper signals, it would engraft as a primary tumor, corresponding to a post-implantation blastocyst. i-CSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 200 publications
(402 reference statements)
3
89
0
Order By: Relevance
“…Much scientific evidence indicated that the expression of genes responsible for normal embryo development was aberrant and contributed to carcinogenesis. [22][23][24] In the past years, HOX genes emerged as transcriptional regulators responsible for embryogenesis and were involved in the development of various cancers. 4 As an essential part of HOXA family genes, HOXA10 expression was crucial for ensuring normal development and differentiation of hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Much scientific evidence indicated that the expression of genes responsible for normal embryo development was aberrant and contributed to carcinogenesis. [22][23][24] In the past years, HOX genes emerged as transcriptional regulators responsible for embryogenesis and were involved in the development of various cancers. 4 As an essential part of HOXA family genes, HOXA10 expression was crucial for ensuring normal development and differentiation of hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the same processes can be hijacked by tumor cells during cancer development (4). Indeed, several analogies have been drawn between organismal development and tumorigenesis (5).…”
Section: The Epithelial To Mesenchymal Transition (Emt) Processmentioning
confidence: 99%
“…These results support the hypothesis of embryonic basis of cRc carcinogenesis, which is depended on colonic stem cells via transformation to a more juvenile proliferation state, turning them into cScs and finally leading to CRC. A very recent theoretical model tries to unify the cSc and embryonic hypothesis in the context of carcinogenesis based on the principles of gastrulation (343). According to this proposal, a normal adult differentiated cell can transform into a cSc, after undergoing deprogramming (dedifferentitation) and reprogramming in the lack of genomic stability.…”
Section: The Embryological Hypothesis Of Colorectal Carcinogenesismentioning
confidence: 99%
“…In distant metastatic niches, cSc3s would be localized in a dormant state as an effect of hypoxia and EMT signaling. contrarily, when normoxia or MET signaling prevail in the metastatic niche, a cSc3/cSc1 reversion would then be induced, and the newly formed cSc1s, as tumor-initiating cells would reproduce the same cell hierarchy of the primary tumor as macro-metastases (343).…”
Section: The Embryological Hypothesis Of Colorectal Carcinogenesismentioning
confidence: 99%